1994
DOI: 10.1111/j.1365-2621.1994.tb14667.x
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Histological Structure of Carrots Frozen at a Programmed Rate and thawed in an Electrostatic Field

Abstract: To investigate the most suitable rate of freezing and method for thawing, raw and blanched carrots were frozen with LN, (freezing rate: -5°C or -2Y%in, final temp: -30°C) using a program freezer (PF), or were frozen using conventional freezers (F: -8O"C, -30°C and -20°C). Then, they were thawed in five different ways: electrostatic thawing (ET, -3"C, 17 hr); -3"C, 17 hr, YC, 17 hr, 2O"C, 30 min; lOO"C, 3 min. Firmness of thawed carrots and amount of undamaged tissues by LM and TEM observations were greatest to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…The textural changes in carrots during blanching have been investigated by Fuchigami et al, 12 Glasscock et al 32 and Rahman et al 14 Glasscock et al 32 found higher shear values for carrots following microwave blanching than following water blanching after one month of frozen storage. The same tendency in the textural attributes was seen in the present study.…”
Section: Discussion and Conclusion Blanchingmentioning
confidence: 99%
“…The textural changes in carrots during blanching have been investigated by Fuchigami et al, 12 Glasscock et al 32 and Rahman et al 14 Glasscock et al 32 found higher shear values for carrots following microwave blanching than following water blanching after one month of frozen storage. The same tendency in the textural attributes was seen in the present study.…”
Section: Discussion and Conclusion Blanchingmentioning
confidence: 99%
“…The optimum freezing rate of carrots has been established as -YC/min, using a programmable freezer and based on texture and histological structure. (Fuchigami et al, 1994(Fuchigami et al, , 1995b. Chinese cabbage leaves cracked when frozen rapidly with liquid nitrogen (LN,).…”
Section: Introductionmentioning
confidence: 99%
“…Cell size and shape are known to change with growth, 3 maturation and ripening 4,5 and turgor. 6 These and other studies used a range of microscopies 7 to image the cells such as light after staining and embedding and transmission electron after staining and cryo-scanning electron after etching.…”
Section: Introductionmentioning
confidence: 99%